Effectiveness of upper arm and breathing exercises to improve inflammatory markers in severe COVID-19 patients - Tarigan, Amira P.; Firdaus, Ruby; Pandia, Pandiaman; Pradana, Andika; Abdullah, Muntasir; Sinaga, Sudirman P.; Wijanarko, Wahyu; Triwahyudi, Bibit; Vera, Yeni; Maryaningsih, Maryaningsih; Eyanoer, Putri C.; Listyoko, Aditya S. (Narra Sains Indonesia, 2024)
Studies have suggested associations between inflammatory markers with the severity of coronavirus disease 2019 (COVID-19). Therefore, exercises that could reduce the level of inflammatory markers might be beneficial. The aim of this study was to determine the effect of upper arms and breathing exercises on inflammatory markers such as ferritin, lactate dehydrogenase (LDH), and C-reactive protein (CRP) in severe COVID-19 patients. A quasi-experimental with pre-test and post-test control group design was conducted among severe COVID-19 aged 18–70 years old, with or without comorbidities. Baseline data of inflammatory markers (ferritin, LDH, and CRP) were measured before the exercises and repeated post-exercise. The upper arm and breathing exercises were performed for ten days, twice a day (morning and evening) for ten minutes. A paired Student t-test was used to assess the changes in the inflammatory markers’ levels. Our data indicated that levels of ferritin and CRP were not significantly different between pre- and post-exercise. However, the level of LDH decreased significantly from 481.35 U/L to 331.80 U/L (p=0.001). This study highlights that pulmonary rehabilitation exercises might be beneficial to enhance the recovery process in severe COVID-19 patients.